2014
DOI: 10.1371/journal.pone.0094312
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy Results in Variable Changes in Nociception, Mood and Depression in Adult Female Rats

Abstract: Decline in the ovarian hormones with menopause may influence somatosensory, cognitive, and affective processing. The present study investigated whether hormonal depletion alters the nociceptive, depressive-like and learning behaviors in experimental rats after ovariectomy (OVX), a common method to deplete animals of their gonadal hormones. OVX rats developed thermal hyperalgesia in proximal and distal tail that was established 2 weeks after OVX and lasted the 7 weeks of the experiment. A robust mechanical allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 58 publications
8
70
0
Order By: Relevance
“…Irrespective of CUS condition, ovariectomy increased passive-coping behaviour in the tail suspension test, and under non-CUS conditions, this effect was prevented by E2, DPN, and PPT treatments. This finding is consistent with previous reports showing that ovarian hormone deprivation alone increases depressive-like behaviour in both rats and mice, at least in the short term (Bekku and Yoshimura, 2005;Li et al, 2014). Importantly, our findings implicate both ERα and β in mediating the effects of estradiol to promote active-coping behaviour under non-stress conditions.…”
Section: Cus Condition and Behavioural Testsupporting
confidence: 93%
“…Irrespective of CUS condition, ovariectomy increased passive-coping behaviour in the tail suspension test, and under non-CUS conditions, this effect was prevented by E2, DPN, and PPT treatments. This finding is consistent with previous reports showing that ovarian hormone deprivation alone increases depressive-like behaviour in both rats and mice, at least in the short term (Bekku and Yoshimura, 2005;Li et al, 2014). Importantly, our findings implicate both ERα and β in mediating the effects of estradiol to promote active-coping behaviour under non-stress conditions.…”
Section: Cus Condition and Behavioural Testsupporting
confidence: 93%
“…Ovarian hormones not only play an important role in reproductive behavior, but also involve in emotion, memory, neuronal survival and perception of somatosensory stimuli 3,11 . On the other hand, mood disorders in women have been reported to be more common than men 12 .…”
Section: Discussionmentioning
confidence: 99%
“…This fact has been attributed to hormonal changes in premenstrual and postpartum periods which have also been confirmed in hypoestrogenic conditions occurred during medical surgery or menopause 13 . Using FST and tail suspension tests, an increase in immobility time and a decrease in active behaviors were reported 2-4 weeks after ovariectomy in both rats and mice which were partially reduced by estradiol injection 11,14 . In the present study, the ovariectomized rats showed higher immobility and lower active times compared to sham operated ones when the animals were examined in FST.…”
Section: Discussionmentioning
confidence: 99%
“…Little literature information is specifically aimed to investigate the influence of menopausal transition on mood-related behaviors in rodents; generally, the effect of spontaneous and surgical-induced menopause on mood-related behaviors is the main focus of preclinical studies. For instance, in forced swimming and tail suspension tests, increases in immobility time which were thought to be indicative of depressive-like behaviors have been observed some weeks after ovariectomy in both rats and mice [39][40][41][42][43][44]. Previously, our research group showed that 20-month old females (which are in post-menopause) are more depressed than adult female rats when assessed in the forced swimming test [34].…”
Section: Discussionmentioning
confidence: 99%